Need Analysis to Develop Global Warming e-Module Integrated Problem Bases Learning Model to Improve Students' 21st Century Skills - Hamida Syukran Hayati; Asrizal Asrizal (Department of Physics Universitas Negeri Padang, 2023)
The challenges of globalization require students to have skills or skills, especially skills of 21st century. The skills of 21st century that students must increase are the 4C skills, including: thinking in critical, creative, collaboration and communication. The research aim was to analyze the need for the making of an e-module on global warming integrated with the PBL model to increase students' skills of 21st century. In the research there were three something investigated, namely physics teachers, physics lesson plans, physics materials of teaching, and students of class XI IPA. The research subjects were 4 physics teachers and 33 people class XI SMA students Negeri 13 Padang. The techniques for data collection used in this research were interviews, documentation and 21st century skills tests. The collected of data by appropriate instruments were analyzed using techniques of descriptive statistical analysis. Based on data analysis, the results obtained included: 1) physics learning could not be carried out properly, 2) the learning objectives developed had not been able to help students achieve learning behavior, 3) analysis of the students characteristics found that motivation, interest, and independence of students are in the less category, 4) analysis of students' 21st century skills found that the initial skills of thinking in critical, creative, collaboration and communication of students are in the less category, 5) analysis of student learning outcomes it is found that midterm exam scores are still in the deficient category.